Pilomatrixoma of the Eyelid - Coban, Deniz Turgut; Cilingir, Arzu; Beden, Umit (Turkish Ophthalmological Society, 2010)
Pilomatrixoma is an uncommon benign skin neoplasm of the hair follicle. It can occure almost anywhere in the body. However it has a propensity to occur in the head and neck region especially the eyelid or eyebrow. It is more frequent in children and adolescents. In this study, we report a 65 years old case with pilomatrixoma in lower eyelid.
Keywords: Pilomatrixoma; Eyelid